2003
DOI: 10.1111/j.1365-2621.2003.tb05746.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Properties of Herring (Clupea harengus) Byproduct Hydrolysates

Abstract: The functional, nutritional, and antioxidative properties of hydrolyzed herring and herring byproducts (head and gonad) were evaluated. All freeze-dried herring fish protein hydrolysate (FPH) powders were light yellow and contained 77% to 87% protein. The degree of hydrolysis was 18.3%, 13%, 13%, and 10.1%, respectively, for head, whole fish, body, and gonad after 75 min digestion. All FPH powders had desirable essential amino acid profiles and mineral contents. The emulsifying capacity and stability of all FP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
142
5
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(191 citation statements)
references
References 28 publications
33
142
5
5
Order By: Relevance
“…The apparent metal ions could act as pro-oxidants in the hydrolysate. Sathivel et al (2003) reported that K + , Mg 2+ , Na + and Ca 2+ were abundant in herring and herring byproduct hydrolysates and varied with the substrate used. Fish protein hydrolysates usually contain a moderate NaCl content due to salting for conservation or pH adjustments during the pH shift process.…”
Section: Mineral Contentmentioning
confidence: 99%
“…The apparent metal ions could act as pro-oxidants in the hydrolysate. Sathivel et al (2003) reported that K + , Mg 2+ , Na + and Ca 2+ were abundant in herring and herring byproduct hydrolysates and varied with the substrate used. Fish protein hydrolysates usually contain a moderate NaCl content due to salting for conservation or pH adjustments during the pH shift process.…”
Section: Mineral Contentmentioning
confidence: 99%
“…Effective utilization of this waste would be a promising approach to reduce such a problem as well as earn revenue for its application in food industry. Protein hydrolysates from different fish species such as mackerel (Wu et al 2003), herring (Sathivel et al 2003), tuna cooking juice (Jao and Ko 2002) and black soy bean (Shih et al 2002) have been found to show antioxidative activity against peroxidation of lipids or fatty acids. Different initiative for recovery of protein and amino acids (Mandeville et al 1992), colourants (Chen and Meyers 1982), flavourants (Pan 1990) and chitin, chitosan (Coward-kelly et al 2006) from shrimp head and shell has been undertaken of which enzymatic hydrolysis approach was effective (Ruttanapornvareesakul et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The WHO food safety unit has given high priority for the research in food fermentation, as it will improve the food safety by controlling the growth and activity of pathogens in foods. Moreover, fermented food products are a good source of peptides and amino acids (Rajapakse et al 2005;Sathivel et al 2003). Amongst indigenous fermented products, fermented fishery products have been widely consumed in Southeast Asia as main dishes or condiments, due to their delicacy and high nutritional properties.…”
Section: Introductionmentioning
confidence: 99%